2021
DOI: 10.1001/jamanetworkopen.2020.36469
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of and Factors Associated With Nurse Burnout in the US

Abstract: Key Points Question What were the most recent US national estimates of nurse burnout and associated factors that may put nurses at risk for burnout? Findings This secondary analysis of cross-sectional survey data from more than 3.9 million US registered nurses found that among nurses who reported leaving their current employment (9.5% of sample), 31.5% reported leaving because of burnout in 2018. The hospital setting and working more than 20 hours per week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
236
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(260 citation statements)
references
References 26 publications
15
236
0
9
Order By: Relevance
“…Burnout, depression, and high rates of job dissatisfaction continue to plague the nursing workforce (Melnyk et al, 2021; Shah et al, 2021). Research has demonstrated such mental states as being associated with lower patient satisfaction (Brooks Carthon et al, 2021), increased medical errors (Hall, Johnson, Watt, Tsipa, & O’Conner, 2016; Melnyk et al, 2018, 2021), and increased costs related to job turnover (Shanafelt, Goh, & Sinsky, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Burnout, depression, and high rates of job dissatisfaction continue to plague the nursing workforce (Melnyk et al, 2021; Shah et al, 2021). Research has demonstrated such mental states as being associated with lower patient satisfaction (Brooks Carthon et al, 2021), increased medical errors (Hall, Johnson, Watt, Tsipa, & O’Conner, 2016; Melnyk et al, 2018, 2021), and increased costs related to job turnover (Shanafelt, Goh, & Sinsky, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A large American survey showed that, even before the pandemic, mental health problems such as burnout were cited by more than 30% of nurses who left their jobs, and that those who worked more than 40 hours per week were three times more likely to cite burnout as a reason for leaving their jobs. In addition, about two-thirds of respondents who had left or who considered leaving their jobs because of burnout attributed the causes to a stressful work environment or understaffing [47]. A Québec report published on September 2021 by the state commissioners of the nursing profession, concluded that to be able to offer quality care to the population, nurses must benefit from working conditions that respect their health, safety and integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals often experience burnout (Chemali et al, 2019;Dubale et al, 2019). The results of the study revealed that nurses around the world have high burnout prevalence rates (Hailay et al, 2020;Shah et al, 2021;Woo et al, 2020). Worldwide studies on nurse burnout syndrome are often found in emergency or critical care settings have proved that burnout is a common problem in many countries (Adriaenssens et al, 2015; Alharbi et al, 2016;Hamed et al, 2020;Nobre et al, 2019).…”
Section: Introductionmentioning
confidence: 95%